Pengaruh Kualitas Pelayanan Terhadap Tingkat Kepuasan Wajib Pajak: Studi Empiris Di KPP Pratama Kebon Jeruk Satu Tahun 2015 - Adang, Ferry (Ultimaccounting Jurnal Ilmu Akuntansi, 2017)
The purpose of this research is to determine empirically whether the service quality (tangibles, reability, responsiveness, assurance, and empathy) affect taxpayer's satisfication. This research was conducted by distributing 255 pieces of questionnaires to KPP Pratama Kebon Jeruk Satu. Questionnaires were returned and in the content of 235 pieces and are all used in this research. Multiple Linear Regression was used to the test of hypothesis. The result of this research showed that tangibles, reability, responsiveness, assurance, and emphaty had significant influence in taxpayer's satisfication. Keywords: Taxpayer's Satisfication, Tangibles, Reability, Responsiveness, Assurance, Empathy